2016
DOI: 10.1007/s12031-015-0707-2
|View full text |Cite
|
Sign up to set email alerts
|

Retinal and Optic Nerve Damage is Associated with Early Glial Responses in an Experimental Autoimmune Glaucoma Model

Abstract: It is well established that the immunization with ocular antigens causes a retinal ganglion cell (RGC) decline, which is accompanied by glia alterations. In this study, the degenerative effects of the immunization with an optic nerve homogenate (ONA) and its purified compound S100 were analyzed on retinas and optic nerves. Since a participation of glia cells in cell death mechanisms is currently discussed, rats were immunized with S100 or ONA. At 14 and 28 days, immune-histological and Western blot analyses we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
101
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(109 citation statements)
references
References 45 publications
4
101
0
3
Order By: Relevance
“…In previous studies of our group we could demonstrate that apoptotic processes occur in the retina as early as 14-22 days after ONA immunization [6], which might induce tenascin-C remodelling. Also, optic nerve degeneration was noted in the EAG model at days 14 and 28 [34,72]. Other studies have already demonstrated that tenascin-C expression is highly associated with glial scar formation.…”
Section: Discussionmentioning
confidence: 93%
“…In previous studies of our group we could demonstrate that apoptotic processes occur in the retina as early as 14-22 days after ONA immunization [6], which might induce tenascin-C remodelling. Also, optic nerve degeneration was noted in the EAG model at days 14 and 28 [34,72]. Other studies have already demonstrated that tenascin-C expression is highly associated with glial scar formation.…”
Section: Discussionmentioning
confidence: 93%
“…The optic disc appeared without pathological findings in all animals up to 6 weeks after immunization but importantly, we observed a significant demyelination of the optic nerve and reactive gliosis, which often accompanied the IgG accumulations or appeared in co-localization with IgG-deposition and fragmented nuclei (Fig. 5 E) (Joachim et al, 2012;Noristani et al, 2016).…”
Section: Autoreactive Igg Antibodies Induce Glaucomatous-like Damage mentioning
confidence: 76%
“…Further studies from Joachim et al also demonstrated strong microglial involvement and hints for the caspase-3 mediated apoptosis pathway in the EAG model without any elevation of intraocular pressure (Joachim et al, 2012(Joachim et al, , 2014Noristani et al, 2016). Retinal IgG accumulations were often accompanied in co- Retinal sections were immunostained for IgG accumulations and counterstained with haematoxylin.…”
Section: Autoreactive Igg Antibodies Induce Glaucomatous-like Damage mentioning
confidence: 97%
See 1 more Smart Citation
“…37 Moreover, RGC loss after immunization with retinal antigens is accompanied by antibody depositions and increased levels of microglia. [38][39][40]…”
Section: Autoimmune Involvement In Glaucoma Pathogenesismentioning
confidence: 99%